From giving birth to paid labor: The effects of adult education for prime-aged mothers - Annette Bergemann; Gerard J. van den Berg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
Women without work after childbirth are at risk of losing their connection to the labor market. However, they may participate in adult education programs. We analyze the effect of this on the duration to work and on the wage rate, by applying conditional difference-in-differences approaches. We use Swedish matched longitudinal register data sets covering the full population. The Swedish adult education program is unprecedented in its size, and enrollment is universally available at virtually no cost. We focus on low-skilled women who have recently given birth. We take account of program accessibility, selection issues, course heterogeneity, the income received during adult education, parental leave, and child care fees. Adult education shows positive effects for the unemployed with respect to both the employment probability and wages. To explain the actual program participation rate, we model the enrollment decision from the mothers' point of view, using the estimates to calibrate a job search model. We conclude that non-pecuniary factors cause mothers not to enter adult education.
Keywords: H43; J68; J64; J24; C14; 330; evaluation of adult education; job search model; female labor supply; wages; participation; unemployment; schooling; conditional difference-in-differences